Estimates of free-tropospheric NO2 and HCHO mixing ratios derived from high-altitude mountain MAX-DOAS observations at midlatitudes and in the tropics - S. F. Schreier; A. Richter; F. Wittrock; J. P. Burrows (Atmospheric Chemistry and Physics, 2016)
In this study, mixing ratios of NO2 (XNO2) and HCHO (XHCHO) in the free troposphere are derived from two multi-axis differential optical absorption spectroscopy (MAX-DOAS) data sets collected at Zugspitze (2650 m a.s.l., Germany) and Pico Espejo (4765 m a.s.l., Venezuela). The estimation of NO2 and HCHO mixing ratios is based on the modified geometrical approach, which assumes a single-scattering geometry and a scattering point altitude close to the instrument altitude. Firstly, the horizontal optical path length (hOPL) is obtained from O4 differential slant column densities (DSCDs) in the horizontal (0°) and vertical (90°) viewing directions. Secondly, XNO2 and XHCHO are estimated from the NO2 and HCHO DSCDs at the 0° and 90° viewing directions and averaged along the obtained hOPLs. As the MAX-DOAS instrument was performing measurements in the ultraviolet region, wavelength ranges of 346–372 and 338–357 nm are selected for the DOAS analysis to retrieve NO2 and HCHO DSCDs, respectively. In order to compare the measured O4 DSCDs and moreover to perform some sensitivity tests, the radiative transfer model SCIATRAN with adapted altitude settings for mountainous terrain is operated to simulate synthetic spectra, on which the DOAS analysis is also applied. The overall agreement between measured and synthetic O4 DSCDs is better for the higher Pico Espejo station than for Zugspitze. Further sensitivity analysis shows that a change in surface albedo (from 0.05 to 0.7) can influence the O4 DSCDs, with a larger absolute difference observed for the horizontal viewing direction. Consequently, the hOPL can vary by about 5 % throughout the season, for example when winter snow cover fully disappears in summer. Typical values of hOPLs during clear-sky conditions are 19 km (14 km) at Zugspitze and 34 km (26.5 km) at Pico Espejo when using the 346–372 (338–357 nm) fitting window. The estimated monthly values of XNO2 (XHCHO), averaged over these hOPLs during clear-sky conditions, are in the range of 60–100 ppt (500–950 ppt) at Zugspitze and 8.5–15.5 ppt (255–385 ppt) at Pico Espejo. Interestingly, multi-year-averaged monthly means of XNO2 and XHCHO increase towards the end of the dry season at the Pico Espejo site, suggesting that both trace gases are frequently lifted above the boundary layer as a result of South American biomass burning.